The Capitalization of Public Services and Amenities into Land Prices: Empirical Evidence from German Communities - Alexander Ebertz (ifo Institute - Leibniz Institute for Economic Research at the University of Munich, 2008)
Applying the hedonic approach to land prices, this paper investigates the capitalization of public services and pure amenities in a cross section of German communities. Possible spill-over effects from neighboring municipalities are explicitly included in the analysis and prove to be of considerable importance. Estimates of the impacts of local attributes on land prices are obtained taking into account the spatial structure among unobserved variables. The results confirm that differences in land prices can largely be attributed to local conditions and policies. This implies a significant degree of mobility as well as a sizeable valuation of local attributes by German households.
Keywords: C21; H73; R23; 330; Land Prices; Hedonic Regression; Spatial Dependence